(untitled) (Homoeopathy for All, 2022)
Even mild acne can affect one’s emotional health. This is especially true for teenage girls. In studies, teen girls often say that acne makes them feel unattractive. Acne is one of the most common skin conditions in all age groups, especially teenagers. The clinical presentation of acne can range from a mild comedonal form to severe inflammatory cystic acne of the face, chest, and back. This article reviews causes, risk factors, different types, clinical presentation general management including some home remedies management and homoeopathic way of treatment of acne. Homoeopathy treats the person as a whole. It means that homoeopathic treatment focuses on the patient as a person and his pathological condition.